2022
DOI: 10.1007/s10603-022-09522-7
|View full text |Cite
|
Sign up to set email alerts
|

Rocking the Boat: Loot Boxes in Online Digital Games, the Regulatory Challenge, and the EU’s Unfair Commercial Practices Directive

Abstract: The loot box, a feature of online video games, contains randomised virtual items of importance to gameplay. Comparisons are drawn between chance-based loot boxes and the legal and psychological definitions of gambling, leading to concerns that the format may be an unregulated form of quasi-gambling. Globally, several jurisdictions have intervened to control the loot box, some applying national gambling laws, while others have implemented more general rules, an alternative described as “consumer protection”. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…It is possible that the label actually came into effect at the ESRB prior to that date on which NBA 2K21 had its rating published (i.e., that the publication date of NBA 2K21's rating may not have been 13 April 2020 and, if so, must therefore be after said date). PEGI's records showed that NBA 2K21 was released on 4 September 2020, i.e., five months after the label announcement date.…”
Section: Exploratory Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the label actually came into effect at the ESRB prior to that date on which NBA 2K21 had its rating published (i.e., that the publication date of NBA 2K21's rating may not have been 13 April 2020 and, if so, must therefore be after said date). PEGI's records showed that NBA 2K21 was released on 4 September 2020, i.e., five months after the label announcement date.…”
Section: Exploratory Analysismentioning
confidence: 99%
“…Children and other vulnerable consumers (e.g., people experiencing problem gambling issues) might be at particular risk of harm [10,11] . Many countries are considering imposing legal regulation and a few countries have already taken regulatory actions [12][13][14][15][16] . However, in most countries at present, paid loot boxes are specifically regulated only through industry self-regulation [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, half a decade has passed since this issue first entered mainstream discourse. Preoccupation with the gambling law approach to loot box regulation overlooks the possibility of using other existing laws (e.g., consumer protection law) to regulate loot boxes [7] and the potential harms of videogame monetisation (including those not involving randomisation) more broadly [8] . Frankly, today, it matters little whether loot boxes are 'gambling.'…”
Section: A Red Herringmentioning
confidence: 99%
“…Due to a current lack of regulation, vulnerable consumers (e.g., young people and people experiencing problem gambling issues and psychological distress) might be at particular risk [9,10] . Many countries are considering regulating loot boxes [11] , and some have already sought to do so [8,[12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%